2013
DOI: 10.1371/journal.ppat.1003445
|View full text |Cite|
|
Sign up to set email alerts
|

An Extracellular Subtilase Switch for Immune Priming in Arabidopsis

Abstract: In higher eukaryotes, induced resistance associates with acquisition of a priming state of the cells for a more effective activation of innate immunity; however, the nature of the components for mounting this type of immunological memory is not well known. We identified an extracellular subtilase from Arabidopsis, SBT3.3, the overexpression of which enhances innate immune responses while the loss of function compromises them. SBT3.3 expression initiates a durable autoinduction mechanism that promotes chromatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(118 citation statements)
references
References 54 publications
5
111
0
2
Order By: Relevance
“…The phosphorylation status of MPK3 and MPK6 changes dynamically during pathogen infection (16)(17)(18)(19). In search of a regulator of MAPK activation during immunity, we found that an ABA-deficient mutant, aba2, shows enhanced activation of MPK3 and MPK6 after treatment with flg22, a bacterial MAMP (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…The phosphorylation status of MPK3 and MPK6 changes dynamically during pathogen infection (16)(17)(18)(19). In search of a regulator of MAPK activation during immunity, we found that an ABA-deficient mutant, aba2, shows enhanced activation of MPK3 and MPK6 after treatment with flg22, a bacterial MAMP (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Previous studies in plants associated some subtilases with the defense response to pathogen attack, like the subtilase SBT3.3 in A. thaliana (Ramírez et al, 2013), the P69 in S. lycopersicum (Tornero et al, 1996; Jordá et al, 1999) and the cucumisin in grapevine (Figueiredo et al, 2008, 2012). The subtilase genes from V. vinifera were blasted against the A. thaliana genome (TAIR database, https://www.arabidopsis.org/) and the tomato genome (SolGenomics database, https://solgenomics.net/) to retrieve the grapevine sequences presenting higher sequence similarity to A. thaliana SBT3.3 and tomato P69 genes.…”
Section: Methodsmentioning
confidence: 98%
“…P69 was also the first plant subtilase for which two protein substrates were identified, systemin (Schaller and Ryan, 1994) and the leucine-rich repeat protein (LRP; Tornero et al, 1996), although the consequences of these substrates processing events for plant pathogen interaction still remain unknown. More recently, Ramírez and co-workers have identified a SBT3.3 gene from A. thaliana as encoding a serine protease homolog to the P69C subtilase from tomato and associated its function in immune priming responses (Ramírez et al, 2013). Also, in S. tuberosum , expression profile analysis of detached potato leaves after P. infestans infection or after BABA or BTH treatment highlighted an expression increase of several subtilases genes (Norero et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The process is initiated through the Arabidopsis subtilase SBT3.3, a proteolytic extracellular enzyme, which is involved in activation of chromatin remodeling, covalent histone modifications and defense genes become poised for enhanced activation following pathogen attack [3,134]. During priming, BTH increased acetylation of histone H3 at Lys-9 (H3K9ac) and trimethylation of histone H3 at Lys-4 (H3K4me3) in the promoter regions of the transcription factors WRKY6, WRKY29, and WRKY52 [135]. In addition, DNA methylation and histone modifications are regulated by RNA Polymerase V [136] and are involved in the transmission of a priming state or stress memory, suggesting that plants may inherit priming sensitization [137].…”
Section: Priming Effectmentioning
confidence: 99%